The strategy of domestic wastewater management in Kenjeran Surabaya - Wicaksono, Daniel; Slamet, Agus (Sustinere: Journal of Environment and Sustainability, 2017)
Kenjeran is one of the districts in Surabaya with high-risk sanitation based on EHRA Surabaya 2012. Kenjeran has 4 (four) sub-districts that consists of Bulak Banteng, Tanah Kali Kedinding, Sidotopo Wetan, and Tambak Wedi. Bulak Banteng, Tanah Kali Kedinding, and Tambak Wedi have been identified as the areas in which open defecation still happened. The research is descriptive study by using field survey, interview, and comparison of existing condition with standards and regulations. The technical aspect study is conducted by analyzing the needs of wastewater infrastructure facilities based on the volume of domestic wastewater. 80 (eighty) Communal Sewage Treatment Plant (STP) were designed to solve domestic wastewater handling in 4 (four) sub-districts. Each of 80 (eighty) STP was designed to cover 75 – 100 households. The domestic wastewater treatment used Anaerobic Baffled Reactor Technology. An example of STP design was conducted in Dukuh Bulak Banteng with the coverage of 100 households.